Pengembangan Modul Pembelajaran Biologi Berbasis Hots (Higher Order Thinking Skills) pada Materi Sistem Reproduksi - M.Ilham Ramadhan; Indayana Febriani Tanjung; Reflina (Jurnal Dirosah Islamiyah, 2024)
This study aims to determine the level of validity, practicality and effectiveness of biology modules based on HOTS (Higher Order Thinking Skills) on the material of the human reproductive system. This research is a 4-D model of R&D (Research and Development) (Define, Design, Development, and Disseminate). The subjects of the trial conducted in the study consisted of 20 students from class XI-MIA-2 at SMA Negeri 6 Medan. The results showed that the percentage of module validity scores from material experts was 84% ​​with a very valid category. and module experts by 100% with the "very valid" category. Meanwhile, the percentage of module practicality scores from biology teachers and students were 100% and 92%, respectively, in the "very practical" category. The effectiveness of the development module based on individual mastery of student learning outcomes has reached classical completeness of 85%. with an average value of 89. From the overall results, it has been included in the valid, practical and effective categories.